Recursos educativos concretos para el desarrollo del pensamiento lógico matemático en los estudiantes de Octavo de Educación General Básica Superior - Vera Labanda, Jhon Carlos (2023)
The current research objective was to analyze specific educational resources that promote the development of mathematical logical thinking in Eighth Grade students in the Superior Basic Education. Therefore, qualitative research with a descriptive scope and documentary type was carried out; the techniques used were documentary review and note-taking, using tools such as search logs, bibliographic cards, and content notes. The main findings indicate that concrete educational resources have to be tangible, contextualized, and supportive of diversity, as a result, fostering active student engagement in the enhancement of mathematical skills. Moreover, their integration into curricular plans as games and puzzles help to the reinforcement of mathematical skills. In conclusion, tangible educational resources must be easy to use and adaptable to different learning styles among students. This allowed the development of a didactic guide incorporating the Rubik's Cube, Soma Cube, and Chess as specific educational resources for the development of mathematical logical thinking. Keywords: Mathematical logical thinking, concrete educational resources, mathematical skills, mathematical competence.